2017
DOI: 10.1245/s10434-017-5813-7
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Prognostic Scoring System Based on Preoperative Sarcopenia Predicts the Long-Term Outcome for Patients After R0 Resection for Gastric Cancer: Experiences of a High-Volume Center

Abstract: The prognostic scoring system combining sarcopenia with the cT and cN system can accurately predict 3-year OS and RFS rates after radical gastrectomy for GC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
82
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(84 citation statements)
references
References 31 publications
0
82
0
2
Order By: Relevance
“…Some of the previous studies, all recruiting patients from Asian populations, suggested an increased risk of death among patients with sarcopenia and GC with hazard ratio (HR) of 1.6‐2.7 . Detailed data from Western countries are not available, but in a mixed population of patients with various gastrointestinal malignancies, including 65 GCs, SMI of sarcopenia did not influence survival .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Some of the previous studies, all recruiting patients from Asian populations, suggested an increased risk of death among patients with sarcopenia and GC with hazard ratio (HR) of 1.6‐2.7 . Detailed data from Western countries are not available, but in a mixed population of patients with various gastrointestinal malignancies, including 65 GCs, SMI of sarcopenia did not influence survival .…”
Section: Discussionmentioning
confidence: 95%
“…Another important element for the clinical application of SMI as a predictive and prognostic biomarker is related to the cut‐off values used to define sarcopenia. Values used previously to identify GC patients with impaired postoperative outcomes ranged from 32 to 52.4 for males and 28.6 to 41 for women. However, these studies used various statistical approaches to estimate the optimum cut‐off points, predominantly the most significant P values discriminating survival, or they used values adopted from other studies .…”
Section: Discussionmentioning
confidence: 99%
“…So far, the cutpoint of sarcopenia has not been uniform worldwide . In Western countries, most cutpoints for L3 SMI appear in the upper 30 cm 2 /m 2 in women and 40 cm 2 /m 2 and low 50 cm 2 /m 2 in men, which are higher than that of Eastern countries researched . If the Western definitions are applied, the prevalence of sarcopenia in our study is about 90.7%.…”
Section: Discussionmentioning
confidence: 51%
“…Single‐slice muscle area at the third lumbar vertebra strongly correlated with the whole‐body volume of muscle tissue and has been extensively used in oncology settings . Based on our previous reports , the optimal cutoff levels for SMI were calculated by the X‐tile software (Yale University, New Haven, CT) . In the current study, preoperative sarcopenia was defined as follows: for men, an SMI less than 36.4 cm 2 /m 2 ; for women, an SMI less than 28.4 cm 2 /m 2 .…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation